MECHANISMS OF DEVELOPMENT OF EFFECTIVENESS OF SOCIAL LIFE ADAPTATION OF DISABLED TEENAGERS - Salikhova Gulnoza Makhmudovna (Journals Park Publishing, 2024)
This article is specially enriched in terms of improving the mechanisms of adaptation of deaf and hard of hearing children with disabilities to social life in families.
Keywords: Adaptation to social life, deaf and weak children, implementation of rehabilitation and rehabilitation based on world trends, socialization, disability, family, cooperation, cooperation.